Finite Element-Based Fatigue Behaviour of Springs in Automobile Suspension - Kamal, M.; M. M., Rahman (Universiti Malaysia Pahang, 2014)
This paper presents the fatigue behaviour of springs used in shock absorbers in automobile suspension systems. SAE 9254 is considered as a spring material. Triangular waves with a frequency of 4 Hz and SAE standard suspension loading history (SAESUS) were used for fatigue analysis. Both load histories are scaled according to the maximum and minimum values of deflection, as spring height at full-bump and full-rebound, respectively. Finite element analysis was carried out using the linear static approach. Fatigue analysis was performed using the strain-life method. Absolute maximum principal and critical plane approaches gave results of reasonable accuracy, but later had a considerably longer solution time, while signed von Mises and signed shear approaches gave very conservative results. Thus the absolute maximum principal method is found to be the best suited. The results show that the spring did not fail before 4×105 cycles at 4 Hz for wave time history and 70,000 repeats for SAESUS time history at critical location